Propagation of an endangered gymnosperm tree species (Podocarpus neriifolius D. Don.) by stem cuttings in non-mist propagator - Hossain, Mohammed Aktar; Islam, Mohammed Ashraful; Azad, Mohammed Abul Kalam; Rahman, Mohammad Mahfuzur; Shumi, Wahhida; Ab Shukor, Nor Aini (Universiti Putra Malaysia Press, 2019)
Podocarpus neriifolius D. Don. (Podocarpaceae), an endangered and the only indigenous gymnosperm tree species, grows naturally in Bangladesh. Seed-based propagation of this species is challenging owing to its inadequate number of mother trees and irregular seed-setting attribute from among a few trees scattered throughout the country. This study weighs the significance and multiplication potentials of this species through rejuvenated stem cuttings with or without the application of Indole Butyric Acid (IBA). The rooting ability of the cuttings was evaluated by treating the cutting bases with 0%, 0.2%, 0.4% and 0.8% (w/v) IBA solution prior to place them in a low cost, non-mist propagation system. Steckling performances of the rooted cuttings were evaluated in the nursery conditions. The study found that the species was amenable to rooting with IBA treatments. The highest rooting percentage (61.3 ± 3.3 %; n = 90) and number of roots per cutting (9.8 ± 1.32; n = 90 ) were obtained in the 0.8% IBA treatment; however, the longest root and shoot, as well as the highest initial growth performances were obtained in 0.4% IBA treatment. Therefore, rejuvenated stem cuttings treated with 0.4% or 0.8% IBA solution in a non-mist propagator could potentially be an effective method for the clonal propagation of these tree species.